(3OjhGf Ydj Hf CHj WGdHs - (3GdgGTej, GdbQTj, CHh GdMSf, Ydj Hf CHj WGdH Hf YHO GdeWdH, J (B40 (3gs ((3jfSH dYdj Hf CHj WGdHs)
(3ChdgG (B:s
(3GdfGS ef LgI GdJeKGd CcaGA CHhge BOe hGdCe MhGA (B*** (3hEfeG GegGJ GdfGS ChYjI eSJhOYGJ hddCfSGH CMSGHs
(3BNQgG (B:s
...(3hdG JLRY EPG eG fGH NWH ace ef dWa Naj(B. (3Jes
(3JHUQI GdYfhGf (B:s
(3OjhGf TYQ efShH dYdj Hf CHj WGdHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\295s
(3cTa GdXfhf (B1\802s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs